The Notary's Responsibility for False Statements From the Parties in the Making of Authentic Deeds Reviewed From the UUPA - Ni Nyoman Ayu Sri Ratna Sari; I Made Walesa Putra; I Gusti Ngurah Dharma Laksana (NOTARIIL Jurnal Kenotariatan, 2025)
A Notary is a Public Official who is authorized to make authentic deeds in accordance with the provisions of UUJN Article 1 number 1. Notaries are required to be responsible for the deeds they have made. However, the problem is when the authentic deed made by the Notary contains false information or untruths from the parties. In this case, the Notary only contains data and information provided by the parties. There are no regulations regarding the notary's obligation to validate information from the parties. The purpose of this study is to determine the notary's responsibility when the authentic deed contains false information from the parties and the form of legal protection for notaries against deeds containing false information. The research method used is the normative juridical legal research method which departs from the absence of norms where there is no regulation regarding false information contained in the Notary's deed. Using primary, secondary and tertiary legal materials as well as conceptual approaches and statutory approaches. The results of the study can be concluded that the notary is responsible for the deeds he made both civilly, criminally and administratively. Criminal responsibility lies entirely with the party who provides false information. If a notary intentionally falsifies or manipulates the contents of a deed, he or she can be held legally responsible. Legal protection for notaries can be seen in article 66 of the UUJN where a notary for the benefit of the court, investigation, public prosecutor, or judge with the approval of the Notary Honorary Council.